Juridical Analysis of Abuse of Authority by Project Officials in the Perspective of Criminal Law - Faal Murreyza D; Sami’an Sami’an; Sarwono Hardjomuljadi (International Journal Labs, 2025)
Abuse of authority by project officials in construction works constitutes one of the primary patterns of corruption in public funds management. In practice, numerous cases demonstrate that budget users, delegated budget users, and commitment-making officials bear responsibility not only for tender decisions but also for controlling contract implementation, quality supervision, contract amendments, and payment approvals—creating opportunities for irregularities that result in state financial losses. This study analyzes the juridical construction of abuse of authority by project officials (Penyalahgunaan Wewenang oleh Pejabat Proyek) from the perspective of criminal corruption law, particularly Article 3 of Law No. 31 of 1999 as amended by Law No. 20 of 2001, in relation to the administrative framework under Law No. 30 of 2014 on Government Administration. Employing a normative juridical method with statutory, conceptual, and case approaches, it focuses on the Hambalang National Sport Training Center, e-KTP, and Banggai Laut Stadium projects. Findings reveal that (1) such abuse qualifies as corruption when involving deviation from authority's purpose, mens rea for undue benefit, and proven state losses; (2) boundaries between administrative misconduct and criminal corruption lack clear parameters; and (3) enforcement remains reactive, neglecting systemic governance improvements. Recommendations include clearer guidelines distinguishing errors from abuse, stronger oversight, and reforms to prevent corruption while protecting good-faith officials.